2019
DOI: 10.1111/hae.13841
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the mutation spectrum in a Pakistani cohort of type 3 von Willebrand disease

Abstract: Introduction Type 3 von Willebrand disease (VWD), a severe autosomal recessive hereditary bleeding disorder, is described by the virtual absence of von Willebrand factor (VWF). In consanguineous populations, for example Pakistan, the disease is reported with a higher incidence rate than the worldwide prevalence. Aims This study aims to characterize molecular pathology and clinical profile of type 3 VWD cohort of Pakistani origin. Methods In total, 48 patients were enrolled in the current study. Initially, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
(150 reference statements)
3
9
0
Order By: Relevance
“…VWD3 has been investigated in several studies, and .300 different gene variants have been reported. [7][8][9][10] The majority of these studies involved small groups of patients, and the authors have either focused on clinical symptoms and biochemical phenotype or on the patients' genotype. 6,7 The 3WINTERS-IPS (Type 3 Von Willebrand International Registries Inhibitor Prospective Study) is an investigator-initiated, multicenter, European/Iranian observational study that aims to comprehensively evaluate the clinical symptoms of VWD3 patients, 11 their phenotypic laboratory findings, and the VWF variants, as well as the safety and efficacy of replacement therapy for the treatment and prevention of bleeding manifestations (registered at www.clinicaltrials.gov as #NCT02460458).…”
Section: Introductionmentioning
confidence: 99%
“…VWD3 has been investigated in several studies, and .300 different gene variants have been reported. [7][8][9][10] The majority of these studies involved small groups of patients, and the authors have either focused on clinical symptoms and biochemical phenotype or on the patients' genotype. 6,7 The 3WINTERS-IPS (Type 3 Von Willebrand International Registries Inhibitor Prospective Study) is an investigator-initiated, multicenter, European/Iranian observational study that aims to comprehensively evaluate the clinical symptoms of VWD3 patients, 11 their phenotypic laboratory findings, and the VWF variants, as well as the safety and efficacy of replacement therapy for the treatment and prevention of bleeding manifestations (registered at www.clinicaltrials.gov as #NCT02460458).…”
Section: Introductionmentioning
confidence: 99%
“…Causative VWF variants were identified in all 44 type 3 subjects with 93% of the mutant alleles accounted for, which is consistent with other type 3 VWD studies that have reported between 80%-95% of cases with pathogenic variants. 4,[7][8][9][10] Of the variants identified, 9% were large heterozygous deletions of exon 1-3, exon 4-5, exon 18 and exon 35-38. The exon 4-5 in-frame deletion has been previously reported as the most common deletion in the VWF gene occurring in both type 1 and type 3 VWD.…”
Section: Discussionmentioning
confidence: 99%
“…A thorough genetic evaluation included VWF Sanger sequencing, comparative genomic hybridization (aCGH) and in silico prediction programs. While several large type 3 studies have been previously reported, 4,[7][8][9][10] the results provided here from the Zimmerman Program represents a cohort of VWD families in the U.S. with extensive phenotypic and genotypic data and provides additional insight into the bleeding tendencies, inheritance and phenotypic heterogeneity in families with type 3 VWD.…”
Section: Introduction/backg Roundmentioning
confidence: 99%
“…The VWD diagnosis and classification of the IPs were made based on bleeding symptoms and standard coagulation tests, consistent with ISTH‐SSC VWF guidelines (Sadler et al, 2006). The VWF analysis was before performed in Bonn Haemophilia Center, and the result of the genetic analysis, as well as coagulation tests, has been previously reported (Ahmed et al, 2019; Yadegari et al, 2012). DNA and protein sequence numbering has been done based on the reference sequence: RefSeq NM_000552.4 and NP_000543.2, respectively, and sequence variant descriptions were verified by VariantValidator online tool (https://variantvalidator.org/; accessed on September 20, 2020).…”
Section: Methodsmentioning
confidence: 99%